The Strategy of School Principal in Improving Teacher Performance - El-Faradis, Fayruzah; Hidayati, Nazlah; Maula, Atiqatul (Maharot : Journal of Islamic Education, 2024)
Many things happen in educational fields. In this case especially principle and teachers. Principal have to arrange many strategies in order to improve teacher’s performance. This article aim to describe the strategy conducted by principle in TMI Al-Amien Prenduan and what are obstacles faced by principal in improving teacher performance. This research used qualitative approach, the data collection research used are interview, observation and documentation. The data analyzed by data reduction, data presentation and verification while Data validity checking used triangulation. The result of this research are: the strategy used by principle in improving teacher performance, are; performance founding, supervision, discipline founding, motivation and reward. While the obstacles faced are; the lack of principal assistance in conducting administrative tasks, the lack of teacher motivation, and lack of chance in self-improvement.